Gay fandom and crossover stardom : James Dean, Mel Gibson, and Keanu Reeves - DeAngelis, Michael, 1957- (E-Duke books scholarly collection., 2001)
A case study of James Dean, Mel Gibson, and Keanu Reeves and how they maintain their appeal to both gay and straight audiences.